2008
DOI: 10.1095/biolreprod.107.060038
|View full text |Cite
|
Sign up to set email alerts
|

Xenogenesis in Teleost Fish Through Generation of Germ-Line Chimeras by Single Primordial Germ Cell Transplantation1

Abstract: Primordial germ cells (PGCs) are the only cells in developing embryos with the potential to transmit genetic information to the next generation. PGCs therefore have the potential to be of value for gene banking and cryopreservation, particularly via the production of donor gametes with germ-line chimeras. Currently, it is not clear how many PGCs are required for germ-line differentiation and formation of gonadal structures. In the present study, we achieved complete germ-line replacement between two related te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
166
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 24 publications
6
166
0
6
Order By: Relevance
“…To exclude the influence of somatic cells while simultaneously ensuring that we transplanted PGCs, we isolated PGCs from embryos that had been injected with GFP-nos1 3'UTR mRNA to label the germ cells. We previously showed that a single PGC isolated from a 10-15-somite stage could migrate toward the gonadal region of a host embryo after transplantation (Saito et al, 2008). However, in the earlier study, we did not determine the optimal stage of donor embryo development for isolating PGCs for successful SPT.…”
Section: Optimum Embryo Developmental Stage For Sptmentioning
confidence: 88%
See 3 more Smart Citations
“…To exclude the influence of somatic cells while simultaneously ensuring that we transplanted PGCs, we isolated PGCs from embryos that had been injected with GFP-nos1 3'UTR mRNA to label the germ cells. We previously showed that a single PGC isolated from a 10-15-somite stage could migrate toward the gonadal region of a host embryo after transplantation (Saito et al, 2008). However, in the earlier study, we did not determine the optimal stage of donor embryo development for isolating PGCs for successful SPT.…”
Section: Optimum Embryo Developmental Stage For Sptmentioning
confidence: 88%
“…In many host embryos, the transplanted PGCs successfully migrated toward gonadal anlage. These transplantation experiments showed that viable sperm could be produced in germ-line chimeras between different species, that is, xenogenesis was feasible across species, genus, and family barriers (Saito et al, 2008). In similar fashion, it has been reported that intra-specific germ-line chimeras can be produced by transplanting blastomeres at the blastula stage (Lin et al, 1992;Ciruna et al, 2002;Yamaha et al, 2001;Yamaha et al, 2003;Takeuchi et al, 2001).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Females can also be mated to WT males to produce clutches of embryos without maternal gene products. Germ-line replacement has now been used on a wide variety of fish species and even in cross-species transplants, opening up additional opportunities for research on gamete development (Saito et al 2008;Shimada and Takeda 2008;Goto et al 2012).…”
Section: Maternal-and Paternal-effect Screensmentioning
confidence: 99%